2019
DOI: 10.1007/s10120-019-00937-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery versus conventional care in gastric cancer surgery: a meta-analysis of randomized and non-randomized controlled trials

Abstract: Introduction Enhanced recovery after surgery (ERAS) protocols have been successfully integrated into peri-operative management of different cancer surgeries such as colorectal cancer. Their value for gastric cancer surgery, however, remains uncertain. Methods A search for randomized and observational studies comparing ERAS versus conventional care in gastric cancer surgery was performed according to PRISMA guidelines. Random-effects meta-analyses with inverse variance weighting were conducted, and quality of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 55 publications
7
52
1
Order By: Relevance
“…[23][24][25] However, some studies have raised the concern that early discharge could miss complications and lead to a higher readmission rate. 26,27 Complication rates (13.4%) within 30 days after surgery were comparable to previous conventional studies (13.0%-16.6%) 5,6 and our conventional CP group (9.5%, P = 0.338). The readmission rate (6.3%) in this study was also comparable to previous studies that applied conventional management (3.8%-7.5%), [28][29][30] although it was higher than that of our conventional CP group (0.7%).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[23][24][25] However, some studies have raised the concern that early discharge could miss complications and lead to a higher readmission rate. 26,27 Complication rates (13.4%) within 30 days after surgery were comparable to previous conventional studies (13.0%-16.6%) 5,6 and our conventional CP group (9.5%, P = 0.338). The readmission rate (6.3%) in this study was also comparable to previous studies that applied conventional management (3.8%-7.5%), [28][29][30] although it was higher than that of our conventional CP group (0.7%).…”
Section: Discussionsupporting
confidence: 85%
“…The mean length of hospital stay (4.7 ± 1.3 days) was shorter than our historical cohort that had completed a conventional CP (7.2 ± 2.3 days) and the previous time periods reported for gastric cancer ERAS (6.8 − 9.0 days) . However, some studies have raised the concern that early discharge could miss complications and lead to a higher readmission rate …”
Section: Discussioncontrasting
confidence: 51%
“…However, the differences of interpretative measures (including operative time and blood loss) and the occurrence of complications (including nausea, intestinal obstruction, urinary tract infection, urinary leakage, and deep venous thrombosis) remained no statistical significance. To date, numerous articles have been performed to explore the efficacy and safety of ERAS program in laparoscopic surgery of various diseases, such as colorectal cancer, gastric cancer, bladder cancer, and hepatocellular cancer [17][18][19][20][21]. Ni et al [17] reported 13 RCTs of ERAS program in laparoscopic colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, IL-6 and CRP levels of patients in ERAS group are proved to be lower. Wee et al [18] reported 23 studies (including 14 RCTs) of ERAS program in gastric cancer surgery in 2018 and demonstrated that ERAS program in gastric cancer surgery can reduce hospital stay, costs, surgical stress response, and time to return of gut function as compared to conventional care. Xiao et al [19] reported 16 trails (including 8 retrospective and 8 prospective trials) of ERAS program in bladder cancer surgery in 2019 and showed that ERAS protocols are associated with a faster return of bowel function, reduced incidence of POI, and shorter LOS when compared to SC in patients undergoing RC.…”
Section: Discussionmentioning
confidence: 99%
“…These results may also have been influenced by the clinical pathway of enhanced recovery after surgery (ERAS). The ERAS program reduces the time required for normalization of gut function [18]. With the widespread use of the recent ERAS protocol, fluid and meal intakes were initiated earlier in the latter period of this study.…”
Section: Discussionmentioning
confidence: 99%